The paternal genetic structure of Jingpo and Dai in southwest China - Bingying Xu; Jianxin Guo; Ying Huang; Xueyun Chen; Xiaohua Deng; Chuan-Chao Wang (Taylor & Francis Group, 2019)
Yunnan province harbours substantial genetic, cultural and linguistic diversity, with the largest number of Aborigines in China, but the relationship among these Aborigines remains enigmatic. This study genotyped 45 Y chromosomal single nucleotide polymorphisms (SNPs) of 500 males from two aboriginal cross-border populations, Jingpo and Dai, from Dehong, Yunnan. It is reported that Haplogroup O2a2b1a1-M117 is the dominant lineage in both Jingpo and Dai. The Jingpo people show affinity with Tibeto-Burman speaking populations with a relatively high frequency of Haplogroup D-M174, and the Dai people are generally genetically similar with Tai-Kadai speaking populations with high frequencies of Haplogroup O1a-M119 and O1b1a1a-M95, which is consistent with their language classification.